(untitled) (Scientia Agricola, 2011)
Alternative use of the X-ray test to evaluate seed quality has become increasingly diverse. This study was performed primarily to establish experimental procedures and verify the effectiveness of the X-ray test to detect damage or abnormalities in bell pepper (Capsicum annuum) seed structure associated with germination. Five seed lots each of hybrids Reinger and Sentinel were used. Two hundred seeds per lot were exposed to durations and intensities of X-radiation and visually classified into four categories according to the proportion between the area occupied by the embryo and endosperm in relation to the total cavity area in the internal seed structure, e.g. 0, < 50%, 50-75% and 100%. The last category was subdivided into two others based on the occurrence of morphological abnormalities. Seed samples obtained from different X-ray categories were then submitted to germination test at 25ºC for 14 days and subsequently compared with results of the X-ray analysis. Exposure to a 10 kV radiation for 260 s was the most suitable X-ray dose for visualizing seed structure. Seeds in which the area of the internal cavity occupied by the embryo and endosperm varied from 50-75% produced abnormal seedlings or did not germinate. Full seeds (100% of the internal cavity area occupied) with abnormal structure usually originated defective seedlings. As a consequence, the classification of bell pepper seeds according to the proportion occupied by the seed content (embryo + endosperm) allowed a reliable estimation of the degree of seed physical integrity based on X-ray analysis and its association with germination performance.